Prognostic Value of Long Non-Coding RNAs GUSB Pseudogene 11 in Colorectal Cancer and Its Regulatory Effect on Tumor Progression - Hu, Jia-Rui; Fan, Jie-Ting; Qu, Shao-Bo; He, Xiao-Hua; Liu, Dai-Wei; Wang, Yong-Xia; Wu, Xiao-Yuan; Li, Zhan-Lin (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Colorectal cancer (CRC) is the third most common cancer, and its progression to advanced diagnosis leads to a dismal prognosis. The long non-coding RNA (lncRNA) GUSB Pseudogene 11 (GUSBP11) can act in a variety of cancers. Nevertheless, the potential mechanism of GUSBP11 in CRC has not been reported. The purpose of this study is to investigate the relationship between the role of GUSBP11 expression in CRC progression as well as prognosis. Materials and Methods: Two hundred and fifty-nine CRC patients were recruited. Expression levels of GUSBP11 and downstream target genes in CRC cell lines were evaluated by quantitative reverse transcription polymerase chain reaction. The influence of clinical charac teristics and GUSBP11 on prognosis was evaluated by the proportional hazards model. Cell-Counting-Kit-8 and transwell assays were conducted for detection of CRC cell proliferation, migration, and invasion. Dual luciferase and correlation analyses were used to validate GUSBP11 with predicted genes. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses were performed to analyze downstream gene function and signaling pathways. Results: The expression of GUSBP11 was upregulated in CRC and relevant to the deterioration of prognosis. The CRC cell proliferation, migration, and invasion were inhibited by GUSBP11 silencing. miR-605-3p was the downstream target gene of GUSBP11, and its expres sion is negatively regulated by GUSBP11. Conclusion: Taken together, this study highlights that the inhibition of miR-605-3p by GUSBP11 to regulate the downstream signaling pathway leads to prognostic malignancy and promotes tumor growth in CRC. Cite this article as: Hu J, Fan J, Qu S, et al. Prognostic value of lncRNA GUSBP11 in colorectal cancer and its regulatory effect on tumor progression. Turk J Gastroenterol. 2025;36(11):732-742.